Congenital Cytomegalovirus Infection: Evaluation and Management (Journal of Enam Medical College, 2019)
Congenital cytomegalovirus (CMV) infection is the most common congenital infection worldwide and most individuals are eventually exposed to this agent. In developing countries the seroprevalence in women of reproductive age approximates 100%. Cytomegalovirus (CMV) infection has great importance to obstetriciangynecologists and pediatricians. Despite the heavy disease burden, CMV infection is severely under-diagnosed because the majority (approximately 80%) of affected mothers are asymptomatic. The clinical manifestations of congenital CMV infection vary widely, from asymptomatic infection to potentially life-threatening disseminated disease. Prenatal diagnosis of fetal CMV infection can be made by testing amniotic fluid for cytomegalovirus by amniocentesis. Diagnosis of congenital cytomegalovirus infection in neonates should include real-time PCR of saliva, urine, or both, as soon as possible after birth. Antiviral therapy is not routinely recommended for congenital cytomegalovirus infection. Neonates with life-threatening infection and moderately to severely symptomatic congenital cytomegalovirus disease, CNS involvement is considered for immediate treatment that should be initiated within first month of life.J Enam Med Col 2019; 9(2): 116-126